Social Process of Ethnicity in Urban Area: Case Study Between Chinese Ethnic and Sundanese Ethnic in Bandung City - Mulyadi, Mohammad (Jurnal Bina Praja, 2017)
A city with a multicultural society allows the social processes of ethnicity, either associative or dissociative. Especially in the city of Bandung, the dynamics of social processes of ethnicity between Chinese ethnic and Sundanese ethnic have ups and downs. Based on the idea, the purpose of this study is to describe how the associative and dissociative social process of Chinese ethnic and Sundanese ethnic in Bandung? The research design uses a qualitative approach with case study model. The location of the research was conducted in Bandung. This research produced a description of social relations practices that are associative in the form of cooperative relations if there is a common interest, while in the form of accommodation occurs if the Chinese ethnic embraces Islam. The social process in the form of assimilation and amalgamation can be seen in the field of culture. Meanwhile, social processes that indicate competition, rivalry, and social conflict (dissociative) start from the perspective of stereotypes, prejudices and discriminatory.